Tinjauan Pelaksanaan Rekam Medis Elektronik Rawat Jalan di Rumah Sakit Soeharto Heerdjan - Azzahra, Annisa; Yulia, Noor; Sonia, Dina; Fannya, Puteri (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
The rapid development of information technology has penetrated various sectors of life, including the healthcare sector, and has significantly influenced the advancement of computer-based medical record systems. The utilization of information technology in medical record systems is a strategic step to improve the quality of healthcare services in hospitals. However, in practice, the implementation of Electronic Medical Records (EMR) still faces several challenges, such as the gap between regulation and actual implementation, limited human resources, and suboptimal infrastructure. This study aims to review the implementation of Standard Operating Procedures (SOP), the use of EMR systems, and the inhibiting factors based on the 5M approach (Man, Material, Machine, Method, Money) at Soeharto Heerdjan Hospital. The research method used is descriptive qualitative, conducted through in-depth interviews and observations involving 12 informants, including medical personnel, administrative staff, and IT teams. The results of the study indicate that although SOPs are available and the system is integrated, the implementation is still hindered by work habit factors, limitations of the application system, and inadequate infrastructure support. Therefore, improvements in training, system strengthening, and workflow enhancement are necessary.